2016
DOI: 10.1016/j.biocel.2016.08.012
|View full text |Cite|
|
Sign up to set email alerts
|

Cessation of biomechanical stretch model of C2C12 cells models myocyte atrophy and anaplerotic changes in metabolism using non-targeted metabolomics analysis

Abstract: Studies of skeletal muscle disuse, either in patients on bed rest or experimentally in animals (immobilization), have demonstrated that decreased protein synthesis is common, with transient parallel increases in protein degradation. Muscle disuse atrophy involves a process of transition from slow to fast myosin fiber types. A shift toward glycolysis, decreased capacity for fat oxidation, and substrate accumulation in atrophied muscles have been reported, as has accommodation of the liver with an increased gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Ribel-Madsen et al found that young, healthy low-birth-weight men showed high plasma concentrations of proline and alanine after high-fat overfeeding, probably due to an increase in insulin-resistance and proteolysis in skeletal muscle [ 31 ]. Ilaiwy et al observed that muscle cell atrophy was associated with increased concentrations of proline and alanine together with other metabolites including glutamine in culture media in vitro [ 32 ], again agreeing with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Ribel-Madsen et al found that young, healthy low-birth-weight men showed high plasma concentrations of proline and alanine after high-fat overfeeding, probably due to an increase in insulin-resistance and proteolysis in skeletal muscle [ 31 ]. Ilaiwy et al observed that muscle cell atrophy was associated with increased concentrations of proline and alanine together with other metabolites including glutamine in culture media in vitro [ 32 ], again agreeing with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Alanine and glutamic acid are crucial intermediates of muscle energy metabolism and liver-muscle metabolic interchange under both physiologic and pathologic conditions [51][52][53]. Perturbations in alanine and glutamate circulating pool may be indicative of skeletal muscle dysfunction, and are commonly encountered in age-related chronic conditions and models of muscle atrophy [54,55]. Notably, both alanine and glutamic acid levels were positively associated with insulin resistance and risk of T2DM in several independent study cohorts [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of asparagine, aspartic acid, and glutamic acid observed in persons with PF&Ss may be suggestive of perturbations in muscle energy metabolism associated with muscle wasting. Interestingly, a pattern of metabolic changes accompany muscle remodeling after disuse, including energy substrate accumulation (e.g., asparagine) in atrophied muscles [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%